Ultrasonic evaluation of metoclopramide’s effect on gastric motility in emergency trauma patients - Lin, Huan; He, Jing-Jing; Cai, Zhi-Shi; Lu, Zhi-Wei; Lin, Zhi-Jian; Lin, Xian-Zhong; Huang, Qiao-Wen (Frontiers in Physiology, 2023)
Objective: The present study aimed to use bedside ultrasound to evaluate the effects of metoclopramide on gastric motility in patients being treated for trauma in the emergency department. Methods: Fifty patients underwent an ultrasound immediately after attending the emergency department of Zhang Zhou Hospital due to trauma. The patients were randomly divided into two groups: a metoclopramide group (group M, n = 25) and a normal saline group (group S, n = 25). The cross-sectional area (CSA) of the gastric antrum was measured at 0, 30, 60, 90, and 120 min (T = time). The gastric emptying rate (GER, GER=−AareaTn/AareaTn−30−1×100), GER/min (GER divided by the corresponding interval time), gastric content properties, Perlas grade at different time points, T120 gastric volume (GV), and GV per unit of body weight (GV/W) were evaluated. The risk of vomiting, reflux/aspiration, and type of anesthetic treatment were also evaluated. Results: The differences between the two groups in the CSA of the gastric antrum at each time point were statistically significant (p < 0.001). The CSAs of the gastric antrum in group M were lower than those in group S, and the greatest difference between the two groups occurred at T30 (p < 0.001). The differences between the two groups in GER and GER/min were also statistically significant (p < 0.001); those differences in group M were higher than those in group S, and the greatest differences between the two groups occurred at T30 (p < 0.001). There were no obvious change trends in the properties of the gastric contents and the Perlas grades in either group, and the differences between the two groups were not statistically significant (p = 0.97). The differences between the two groups in the GV and GV/W at T120 were statistically significant (p < 0.001), as was the risk of reflux and aspiration at T120 (p < 0.001). Conclusion: When metoclopramide was used in satiated emergency trauma patients, it accelerated gastric emptying within 30 min and reduced the risk of accidental reflux. However, a normal gastric emptying level was not achieved, which can be attributed to the delaying effect of trauma on gastric emptying.